The entropic force in Reissoner-Nordström-de Sitter spacetime - Li-Chun Zhang; Ren Zhao (Physics Letters B, 2019)
We compare the entropic force between the black hole horizon and the cosmological horizon in Reissoner-Nordström-de Sitter (RN-dS) spacetime with the Lennard-Jones force between two particles. It is found that the former has an extraordinary similarity to the latter. We conclude that the black hole horizon and the cosmological horizon are not pure geometric surface, but have a definite “thickness”, which is proportional to the radius of the horizons. In the case of no external force, according to different initial condition, the relative position of the two horizons will experience first accelerated expansion, then decelerated expansion, or first accelerated contraction, then decelerated contraction. Therefore the whole Universe is oscillating.